IMPLIKASI HUKUM BISNIS TERHADAP PRAKTIK ETIKA BISNIS DI INDONESIA - Rustandi; RR Amanna Dzikirallah LAH (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to analyze the implications of business law on business ethics practices in Indonesia. The research method used is library research, where data is collected from various sources of literature that are relevant to the research topic. The results of the study show that business law has an important role in shaping business ethics practices in Indonesia. Business law regulates rights and obligations arising from agreements and engagements in business practices. In addition, factors such as developments in national development, business ethics, internal and external factors, and legal awareness influence the implementation of business law in ethical and responsible business practices. Therefore, the solutions and recommendations provided to improve the implementation of business law and ethical business practices in Indonesia include strengthening regulations, effective law enforcement, education and awareness, collaboration between the government and the business world, transparency and accountability, and the establishment of a supervisory body. independent. Implementation of this solution is expected to create a business environment that is fair, transparent and with integrity, as well as making a positive contribution to economic development and people's welfare in Indonesia.